2010
DOI: 10.4238/vol9-3gmr789
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of schizophrenia with TPH2 and 5-HTR2A gene polymorphisms in the Malay population

Abstract: ABSTRACT. The serotoninergic system has been implicated in the etiology of schizophrenia and other behavioral disorders. Association studies have focused on the tryptophan hydroxylase 2 gene (TPH2) and the 5-hydroxytryptamine receptor 2A gene (5-HTR2A). We genotyped two single-nucleotide polymorphisms, A1438G of 5-HTR2A and intronic rs1386494 of TPH2 in the Malay population, using a sample size of 289 schizophrenic patients and 130 healthy controls. We found a significant association of A1438G of 5-HTR2A with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…In contrast to TPH1, genetic studies have shown an association between TPH2 and suicidal behavior (Zill et al, 2004b;Li and He, 2006a), major depression (Zill et al, 2004c), panic disorder (Maron et al, 2007), chronic fatigue syndrome (Goertzelet et al, 2006;Smith et al, 2006) and Tourette syndrome (Mössner et al, 2007). However, no evidence has been found for a role of TPH2 in schizophrenia, despite several studies in this area (De Luca et al, 2005a;Higashi et al, 2007;Shiroiwa et al, 2010;Tee et al, 2010;Kim and Yoon, 2011;Zhang et al, 2011). It is noteworthy that a certain number of these studies focused mainly on the rs4570625 (-703G/T), a common polymorphic SNP in the putative promoter (Kennedy et al, 2003) that has been reported to be associated with the attention deficit hyperactivity disorder (ADHD) (Walitza et al, 2005), emotional processing (Herrmann et al, 2007), personality traits, and disorders related to emotional dysregulation (Gutknecht et al, 2007;Reuter et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…In contrast to TPH1, genetic studies have shown an association between TPH2 and suicidal behavior (Zill et al, 2004b;Li and He, 2006a), major depression (Zill et al, 2004c), panic disorder (Maron et al, 2007), chronic fatigue syndrome (Goertzelet et al, 2006;Smith et al, 2006) and Tourette syndrome (Mössner et al, 2007). However, no evidence has been found for a role of TPH2 in schizophrenia, despite several studies in this area (De Luca et al, 2005a;Higashi et al, 2007;Shiroiwa et al, 2010;Tee et al, 2010;Kim and Yoon, 2011;Zhang et al, 2011). It is noteworthy that a certain number of these studies focused mainly on the rs4570625 (-703G/T), a common polymorphic SNP in the putative promoter (Kennedy et al, 2003) that has been reported to be associated with the attention deficit hyperactivity disorder (ADHD) (Walitza et al, 2005), emotional processing (Herrmann et al, 2007), personality traits, and disorders related to emotional dysregulation (Gutknecht et al, 2007;Reuter et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…However, to date, studies of the origins, the migration history as well as relationships among the Orang Asli and Bumiputera of Sarawak are limited (Lian, 2001;Macaulay et al, 2005;Hill et al, 2006;Ang, 2009;Lim et al, 2010) while most existing records are from an anthropological and historical point of view (Wright et al, 1971;Kasimin, 1991;Nicholas, 1996). At the end of the last century, specifically the previous three decades, molecular studies became widely used to study human migration and population relationships (Lutz et al, 1998;Al-Zahery et al, 2003;Endicott, 2003;Kashyap et al, 2003;HUGO Pan-Asian SNP Consortium et al, 2009;Tee et al, 2010). Mitochondrial DNA (mtDNA) analysis is particularly well suited for systematic studies of potentially closely related individuals due to the high molecular rate of evolution and maternal mode of inheritance (Md-Zain et al, 2010a,b;Rosli et al, 2011;Vun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…But the authors themselves remarked that the power of this analysis was very small with 0.18. In Japanese patients as well as in Malay patients no association was found between two variants and one variant of the TPH2 gene respectively, and schizophrenia (Higashi et al, 2007;Tee et al, 2010). In another association study among Japanese patients neither one of the 15 analyzed TPH2 variants nor their haplotypes were significantly associated with schizophrenia (Shiroiwa et al, 2011).…”
Section: Introductionmentioning
confidence: 88%